Optimasi Parameter Proses 3D Printing Terhadap Kuat Tarik Material Filamen PLA + Menggunakan Metode Taguchi - Pratama, Wahyudi Hafizi; -, Hasdiansah; -, Husman (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
FDM (Fused Deposition Modeling) is one of the methods often usen by researchers in 3D printing technology which is used to print filaments products as a materials, due to the easy technique for 3D printing with relatively low production costs. One of the materials that can be processed in a 3D printing machine ia PLA+. Research in tensile testing has been done on PLA and ABS filaments. Meanwhile, tensile testing using PLA+ filaments is still rarely done. From these problems, research is needed to get the optimal process parameters on the 3D printing machine to get the highest tensile strenght value using PLA+ filaments. This research uses the taguchi method, carried out on a PRUSA area model FDM 3D Printing machine with dimensions of 300mm x 300mm x 350mm using a nozzle size of 0.4mm. The material used is PLA + Esun filament with a diameter of 1.75 mm with a variety of printing speed parameters (30 mm/s, 35 mm/s, 40 mm/s, 45 mm/s, 50 mm/s), nozzle temperature (1950C, 2000C, 2050C, 2100C, 2150C), layer thickness (0.10mm, 0.15mm, 0.20mm, 0.25mm, 0.30mm), cooling speed (20%, 40%, 60%, 80%, 100%), orientation (00, 300, 450, 600,900) which will be determined in ideamaker 3.6.1 to produce 75 printed samples. This research aims to determine the optimal tensile strength value. From the research results there is an optimal tensile strength value, namely in experiment 10 with the parameter values of printing speed (35 mm/s), Nozzle Tenperature (2150C), Layer Thickness (0.10mm), Cooling speed (20%), and Orientation (450). with a tensile strength value of 48.1 MPa from 3 replications.